1998
DOI: 10.1161/01.cir.98.23.2513
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Events and Their Reduction With Pravastatin in Diabetic and Glucose-Intolerant Myocardial Infarction Survivors With Average Cholesterol Levels

Abstract: Diabetic patients and nondiabetic patients with impaired fasting glucose are at high risk of recurrent coronary events that can be substantially reduced by pravastatin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
419
2
13

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 879 publications
(442 citation statements)
references
References 19 publications
8
419
2
13
Order By: Relevance
“…Although there were no differences in CVD events (myocardial infarction, stroke, and coronary revascularization) after 3 years between treatment arms in the Diabetes Prevention Program, there were significant reductions in cardiometabolic risk factors in the lifestyle arm, including high triglyceride levels, hypertension, low high‐density lipoprotein, and small dense low‐density lipoprotein 36. In other clinical trials with longer durations of follow‐up, such cardiometabolic risk factor reductions have resulted in reductions in both fatal and nonfatal CVD events 37, 38…”
Section: Discussionmentioning
confidence: 99%
“…Although there were no differences in CVD events (myocardial infarction, stroke, and coronary revascularization) after 3 years between treatment arms in the Diabetes Prevention Program, there were significant reductions in cardiometabolic risk factors in the lifestyle arm, including high triglyceride levels, hypertension, low high‐density lipoprotein, and small dense low‐density lipoprotein 36. In other clinical trials with longer durations of follow‐up, such cardiometabolic risk factor reductions have resulted in reductions in both fatal and nonfatal CVD events 37, 38…”
Section: Discussionmentioning
confidence: 99%
“…The Dubbo Study in the Australian elderly failed to confirm prediction of incident ischemic stroke by diabetes [24]. Moreover, several studies have found that subjects with impaired fasting glucose levels have an increased risk of stroke [3,20,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The UKPDS demonstrated the importance of maintaining good glycaemic control for prevention of the development and progression of complications among patients with type 2 diabetes [44]. Clinical trials have shown that pharmacological treatment of hypertension [45][46][47] and cholesterol reduction with a statin therapy [42,43,[48][49][50] are efficient ways of preventing stroke and other cardiovascular events in patients with diabetes or impaired fasting glucose.…”
Section: Menmentioning
confidence: 99%
“…Landmark secondary prevention studies (4S, CARE, LIPID) have provided strong evidence of the clinical benefits of LDL-lowering in people with diabetes [157,158,159]. The Heart Protection study (HPS) included 5348 people with diabetes and 2279 with no previous CHD [160].…”
Section: Consequences Of the Increase Of Vldl 1 Particlesmentioning
confidence: 99%